2014
DOI: 10.14419/ijbas.v3i3.3142
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of turmeric (Curcuma longa) and garlic (Allium sativum) on Eimeria species in broilers

Abstract: In this study, powders were evaluated for their anticoccidial effects. In in vitro, sporulated oocysts of mixed Eimeria species isolated from naturally infected chickens were randomly assigned to 10, 5, 2.5, 1.25, 0.6, 0.3, 0.2 and 0.08 g turmeric and garlic powders /liter distilled water (g/L). The efficacy of garlic was higher (up to 80%) than turmeric (up to 66.6%) at different concentrations. In the in vivo study, one-day old chicks were divided into 7 equal groups. All groups were infected with 10.000 via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 42 publications
7
15
0
Order By: Relevance
“…In agreement with the current findings, similar in vitro effects of Aloe vera and Aloe spicata on the inhibition of the sporulation of avian coccidian oocysts were reported by Mwale et al [53] and they found that Aloe spicata had higher sporulation inhibition efficacy at 30% concentration (65.42%) while A. vera had the least number of sporulated oocyst at 45% concentration with an inhibition percentage of 62.5%. The 79.35% inhibition efficacy of A. debrana at 30% (w/v) concentration found in this study is consistent with the findings by El-Khtam et al [54] who reported 80% sporulation inhibition effects of garlic powder. Furthermore, El-Khtam et al [54] reported 66% inhibition efficacy of Values in a column followed by the same superscripts are not significantly different (P > 0:05) while different superscripts indicate statistical difference (P < 0:05); AD: Aloe debrana.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In agreement with the current findings, similar in vitro effects of Aloe vera and Aloe spicata on the inhibition of the sporulation of avian coccidian oocysts were reported by Mwale et al [53] and they found that Aloe spicata had higher sporulation inhibition efficacy at 30% concentration (65.42%) while A. vera had the least number of sporulated oocyst at 45% concentration with an inhibition percentage of 62.5%. The 79.35% inhibition efficacy of A. debrana at 30% (w/v) concentration found in this study is consistent with the findings by El-Khtam et al [54] who reported 80% sporulation inhibition effects of garlic powder. Furthermore, El-Khtam et al [54] reported 66% inhibition efficacy of Values in a column followed by the same superscripts are not significantly different (P > 0:05) while different superscripts indicate statistical difference (P < 0:05); AD: Aloe debrana.…”
Section: Discussionsupporting
confidence: 92%
“…The 79.35% inhibition efficacy of A. debrana at 30% (w/v) concentration found in this study is consistent with the findings by El-Khtam et al [54] who reported 80% sporulation inhibition effects of garlic powder. Furthermore, El-Khtam et al [54] reported 66% inhibition efficacy of Values in a column followed by the same superscripts are not significantly different (P > 0:05) while different superscripts indicate statistical difference (P < 0:05); AD: Aloe debrana. Values in a column followed by the same superscripts are not significantly different (P > 0:05) while different superscripts indicate statistical difference (P < 0:05); AP: Aloe pulcherrima.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This in vitro study conducted on garlic supported the previous research that garlic might be used as antcoccidiosis. Garlic has several active compounds including allicin, alliin, ajoene, diallyl sulfide, dithiin, and allylcystein, in which allicin may inhibit E. tenella sporulation in chickens (El-Khtam et al, 2014;Pourali et al, 2014). The other natural plant functioning as an anticoccidiosis is banana stem.…”
Section: Discussionmentioning
confidence: 99%
“…Garlic can be used as antibacterial (Tipu et al, 2002;Safithri et al, 2011), antiparasitic, and anticoccidial agents in sheep (Worku, 2009) and chickens (Pourali et al, 2014;El-Khtam et al, 2014). Garlic and its sulfur compounds, allicin, aliin, ajoene, diallyl sulfide, dithiin, and allylcysteine are reported to have broad antimicrobial activities which can eliminate the negative factor of microbial infections.…”
Section: Introductionmentioning
confidence: 99%